Desain Dan Simulasi Turbin Angin Savonius Dengan Konfigurasi Rotor Tipe L Dan Tipe Helix Sebagai Sumber Listrik Lampu PJU Pelabuhan Perikanan Cikidang Pangandaran Jawa Barat - Wisnu Yudha Santika; Hadi Saputra; Toto Rusianto (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2022)
Cikidang Fishing Port, Pangandaran, West Java is located in the southern region of Java island which is directly opposite the Indian Ocean which has the potential for energy development, one of which is from wind. Wind is one of the natural resources that can be used as an alternative power generation source as a substitute for conventional fuel. From the results of observations on the average wind speed for seven days of v = 4.8 m/s. Based on the results of observations, a vertical axis wind turbine, namely Savonius, is planned as the drive of the power plant generator, with configurations in the shape of the rotor, namely the L type and helix type. In type L with a diameter of 1.1 meters, a height of 1.4 meters can receive kinetic energy = 60.96 Joules which has the potential to produce a rotor power of 110.87 Watts. While in the Helix type with a diameter of 1.1 meters, a height of 1.4 meters can receive 82,63 Joules which has the potential to produce a rotor power of 159.32 Watts. In the static structural simulation, for the Savonius L type wind turbine rotor with Aluminum Alloy material, it showed a total deformation of 12.239 mm, an equivalent elastic strain of 2.1252 x 10-4 mm, and an equivalent stress of 14.973 MPa at a rotor rotation speed of 83.4 RPM with a wind thrust force of 25.4 Newton. The Savonius Helix type wind turbine rotor with Aluminum Alloy material showed a total deformation of 11.74 mm equivalent elastic strain of 1.5941 x 10-5 mm, and an equivalent stress of 18.75 MPa at a rotor rotation speed of 83.4 RPM with a wind thrust force of 34.43 Newton.